Pendidikan Multikultural: Analisis Pengajaran Agama Islam Di Sekolah Dasar Negeri Pangkalpinang, Provinsi Kepulauan Bangka Belitung - Noblana Adib; Rada Rada (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2020)
It is very motivating to see how multicultural education practices in elementary schools in Bangka Belitung Province. In particular, looking at the teaching practice of the teacher of Islamic religious education in the classroom, how teachers use the existing manual book in their daily explanations in the classroom. This type of research is qualitative. Qualitative research is a research procedure that produces descriptive data: speech or writing and the observable behavior of the people (the subject) itself. This approach immediately identifies the setting and the individuals in that setting as a whole. There are six analytical textbooks in this study were written by the same author, Achmad Farichi and Kawan-Kawan, (et al), and all were published in 2007. The publisher of this Islamic religious education textbook is Yudhistira. Therefore, based on observations and reading results in Islamic education textbooks, multicultural education policies do not affect the process of Islamic religious education for teachers at Public Elementary School 10 (RSBI) Pangkalpinang, Bangka Belitung Islands Province. The textbook published by Yudhistira did not mention the influence of educational policies regarding multicultural education that should have been in the text of Islamic education. Sangat menarik melihat bagaimana praktek pendidikan multikultural di sekolah dasar di Provinsi Bangka Belitung. Khususnya melihat praktek pengajaran guru pendidikan agama Islam di kelas, bagaimana guru-guru menggunakan buku panduan yang ada ke dalam penjelasan-penjelasan materi guru tersebut sehari-hari di kelas. Jenis penelitian ini adalah kualitatif, penelitian kualitatif adalah prosedur penelitian yang menghasilkan data deskriptif: ucapan atau tulisan dan prilaku yang dapat diamati dari orang-orang (subjek) itu sendiri. Pendekatan ini langsung menunjukkan setting dan individu-individu dalam setting itu secara keseluruhan. Enam buku teks dianalisis dalam penelitian ini adalah ditulis oleh penulis yang sama, Achmad Farichi dan Kawan-Kawan, (dkk), dan semua diterbitkan pada tahun 2007. Penerbit buku text pendidikan agama Islam ini adalah Yudhistira. Jadi berdasarkan pengamatan dan hasil bacaan pada buku text pendidikan Agama Islam, kebijakan pendidikan multikultural tidak mempengaruhi proses pengajaran pendidikan agama Islam guru di Sekolah Dasar Negeri 10 (RSBI) Pangkalpinang Provinsi Kepulauan Bangka Belitung. Buku text terbitan Yudhistira sama sekali tidak menyebutkan adanya pengaruh kebijakan politik pendidikan mengenai pendidikan multikultural yang semestinya ada pada puku text pendidkan agama Islam.